Sociocognitive Metalexicographic Parameters Of The First Two Editions Of Srpski Rječnik By Vuk Stefanović Karadžić - Šipka, Danko (Slavica Lodziensia, 2017)
The present paper approaches two nineteenth-century editions of Serbian Dictionary by Vuk Stefanović Karadžić from a sociocognitive metalexicographic perspective. Using a triangular communicative model of lexicographic work, the author analyzes sociohistorical factors, lexicographic strategies, and lexicographic elements of the aforementioned dictionary. A special attention is devoted to the diff erences between the two editions, which coincide in time with a broader shift from traditional philology toward linguistics.